Heritage, cultural diversity and education school: education in Programa Mais Educação on heritage - Rodrigo Manoel Dias da Silva; Márcia Amélia Cletes de Moraes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article aims to understand the relationship between heritage education and cultural diversity in Brazilian educational politics, with emphasis on analysis of ministerial documents that belong to heritage education as a theme in Programa Mais Educação. The authors analyze two shifts in the production of sense historically attributed to heritage education and its relationship with contemporary schooling processes.